Culture Of Treatment And Correct Communication - Mavlonova Malika (Euro Asian Journal Publishing, 2025)
Forming a culture of behavior in a person and inculcating the rules of correct communication begins at a young age. Everyone should know the rules of proper behavior in the family and society, shortcomings in communication with adults and children and ways to eliminate them. Proper communication is not just about speaking without using dialect, it is a very complex process.
Keywords: behavior; culture; communication